Development of a virtual learning environment for cardiorespiratory arrest training - Anazilda Carvalho da Silva; Andrea Bernardes; Yolanda Dora Martinez Évora; Maria Célia Barcellos Dalri; Alexandre Ribeiro da Silva; Camila Santana Justo Cintra Sampaio
Abstract OBJECTIVE To develop a Virtual Learning Environment (VLE) aiming at the training of nursing team workers and emergency vehicle drivers in Basic Life Support (BLS) to attend Cardiorespiratory arrest, and to evaluate the quality of its contents among specialists in the area of Emergency and Urgent care. METHOD Applied research of technological development. The methodology used was based on the Instructional Design Model (ADDIE), which structures the teaching-learning planning in different stages (analysis, design, development, implementation and evaluation). The VLE was composed of texts elaborated from bibliographic research, links, edited video from a simulation scenario in the laboratory and questions to evaluate the fixation of the content, organized in modules. RESULTS After its development, it was evaluated as adequate to satisfy the needs of the target public, by eight expert judges, which was made available for electronic access. CONCLUSION The VLE has potential as a tool for training and qualification in BLS, as it can be easily integrated with other pedagogical approaches and strategies with active methodologies.